2023
DOI: 10.53664/jsrd/04-01-2023-08-100-107
|View full text |Cite
|
Sign up to set email alerts
|

IMPACT OF SERVICE QUALITY, CUSTOMER ENGAGEMENT & CUSTOMER SATISFACTION ON CUSTOMER LOYALTY WITH THE MODERATING ROLE OF RELIGIOSITY

Abstract: The study intends to investigate determinants of customers' loyalty to Islamic banks, particularly service quality, customer satisfaction, as well as customer engagement. Moreover, the current study looked into the role of religiosity in moderating the relationship between the observed variables. For the purpose of this study, 335 customers of Islamic banks in Pakistan participated in this survey. This research used the purposive sampling and structural equation modelling to analyses the data. The outcome of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
0
0
Order By: Relevance
“…Thirdly, the relationship between E-CRM and customer loyalty was then investigated to examine whether there was any direct linkage between them and the result findings revealed that there was a significant direct impact of E-CRM on customer loyalty (β =0.259, p<0.001). The findings were found to be in consonance with the past literature (Farmania et al, 2021;Kakesh et al, 2021;Khan & Khawaja, 2013;Mang'unyi et al, 2018;Mousavai et al, 2015;Mulyono & Situmorang, 2018;Rashwan et al, 2019;Salehi et al, 2015;Sasono et al, 2021;Shastri et al, 2020) and revealed that if the banks provide better E-CRM services to their customers, their profitable customer base will expand, and the customers will recommend their banks to their friends and relatives, resulting in positive word-ofmouth. Hence, E-CRM has a significant positive impact on customer loyalty.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Thirdly, the relationship between E-CRM and customer loyalty was then investigated to examine whether there was any direct linkage between them and the result findings revealed that there was a significant direct impact of E-CRM on customer loyalty (β =0.259, p<0.001). The findings were found to be in consonance with the past literature (Farmania et al, 2021;Kakesh et al, 2021;Khan & Khawaja, 2013;Mang'unyi et al, 2018;Mousavai et al, 2015;Mulyono & Situmorang, 2018;Rashwan et al, 2019;Salehi et al, 2015;Sasono et al, 2021;Shastri et al, 2020) and revealed that if the banks provide better E-CRM services to their customers, their profitable customer base will expand, and the customers will recommend their banks to their friends and relatives, resulting in positive word-ofmouth. Hence, E-CRM has a significant positive impact on customer loyalty.…”
Section: Discussionsupporting
confidence: 87%
“…Firstly, the relationship between E-CRM and customer satisfaction was analyzed and the results revealed that E-CRM had a significant positive influence on customer satisfaction (β=0.432, p<0.001). The research findings were found to be in resonance with the past literature (Abdulfattah, 2012;Adnan et al, 2021;Al-Dmour et al, 2019;Chuang et al, 2012;Dehghanpouri et al, 2020;Khan & Khawaja, 2013;Mang'unyi et al, 2018;Mousavai et al, 2015;Mulyono & Situmorang, 2018;Oumar et al, 2017;Rastgar et al, 2019;Upadhyaya, 2020;Zaim et al, 2020) and supported the existing body of knowledge that articulated that the relationship between the customers and service providers gets much stronger when the customers are more satisfied with the services offered by their respective service providers. E-CRM helps in enhancing the long-lasting customer relationships and also stimulating the development of virtual environment which further leads to increased customer satisfaction.…”
Section: Discussionsupporting
confidence: 78%
See 1 more Smart Citation
“…Both affective commitment which contains emotional involvement, normative commitment which contains customer's belief in the bank, as well as continuous commitment. In line with previous research which concludes that customer commitment has a significant effect on customer loyalty (Bahrudin & Zuhro, 2016;Berliana & Sanaji, 2022;Khan et al, 2023;Lapasiang et al, 2017;Lubis et al, 2022;Marliyah et al, 2021;Sudirman & Suasana, 2018). The higher the customer commitment, the higher the customer loyalty.…”
Section: The Effect Of Customer Commitment On Customer Loyaltysupporting
confidence: 86%